Percutaneous management of postoperative Bile leak after hepato-pancreato-biliary surgery: a multi-center experience. Issue 10 (October 2021) - Mosconi, Cristina; Calandri, Marco; Mirarchi, Mariateresa; Vara, Giulio; Breatta, Andrea D.; Cappelli, Alberta; Brandi, Nicolò; Paccapelo, Alexandro; De Benedittis, Caterina; Ricci, Claudio; Sassone, Mirian; Ravaioli, Matteo; et al.
Abstract: Background: Bile leak (BL) after hepato-pancreato-biliary (HPB) surgery is associated with significant morbidity and mortality. Aim of this study was to evaluate effectiveness and safety of percutaneous transhepatic approach (PTA) to drainage BL after HPB surgery. Methods: Between 2006 and 2018, consecutive patients who were referred to interventional radiology units of three tertiary referral hospitals were retrospectively identified. Technical success and clinical success were analyzed and evaluated according to surgery type, BL-site and grade, catheter size and biochemical variables. Complications of PTA were reported. Results: One-hundred-eighty-five patients underwent PTA for BL. Technical success was 100%. Clinical success was 78% with a median (range) resolution time of 21 (5–221) days. Increased clinical success was associated with patients who underwent hepaticresection (86%, p = 0, 168) or cholecystectomy (86%, p = 0, 112) while low success rate was associated to liver-transplantation (56%, p < 0, 001). BL-site, grade, catheter size and AST/ALT levels were not associated with clinical success. ALT/AST high levels were correlated to short time resolution (17 vs 25 days, p = 0, 037 and 16 vs 25 day, p = 0, 011, respectively) Complications of PTA were documented in 21 (11%) patients. Conclusion: This study based on a large cohort of patients demonstrated that PTA is a valid and safe approach in BL treatment after HPB surgery.